Tajikistan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in the Republic of Tajikistan during 1994-97. In 1996, the authorities embarked on their first comprehensive effort at economic reform, supported by financial assistance from the World Bank and the IMF. Although implementation was uneven, the authorities were successful in achieving a degree of macroeconomic stability during the first three quarters of 1996; progress was also made on structural reforms. However, confronted with substantial unanticipated expenditures, the budget deficit increased substantially in late 1996 and the first half of 1997.